Influence of inclusions with Mg deoxidation on the microstructure in the heat-affected zone of steel plates after high-heat-input welding - Long-yun XU; Jian YANG; Rui-zhi WANG (工程科学学报, 2020)
The effects of inclusions on the microstructure and toughness of the heat-affected zone (HAZ) in steel plates with Mg deoxidation after high-heat-input welding were investigated in the present study. The results indicate that the morphologies of MgO–MnS complex inclusions in steel are changed obviously with the addition of Al. When containing 0.001% Al (mass fraction), the inclusions consist of a central single MgO particle and an outside MnS phase. When containing 0.020% Al, they are comprised of several small MgO particles entrapped by the MnS phase. Because the former inclusion can nucleate intragranular acicular ferrites (IAFs) and the latter is non-nucleant, the main intragranular microstructures in the HAZs are ductile IAFs and brittle ferrite side plates, respectively. Therefore, the HAZ toughness of the steel plate without Al addition after a high-heat-input welding of 400 kJ·cm−1 is significantly better than that of the steel plate with Al addition.